Lifetime risk, life expectancy, and years of life lost to type 2 diabetes in 23 high-income jurisdictions: a multinational, population-based study. Issue 11 (November 2022) - Tomic, Dunya; Morton, Jedidiah I; Chen, Lei; Salim, Agus; Gregg, Edward W; Pavkov, Meda E; Arffman, Martti; Balicer, Ran; Baviera, Marta; Boersma-van Dam, Elise; Brinks, Ralph; Carstensen, Bendix; et al.
Summary: Background: Diabetes is a major public health issue. Because lifetime risk, life expectancy, and years of life lost are meaningful metrics for clinical decision making, we aimed to estimate these measures for type 2 diabetes in the high-income setting. Methods: For this multinational, population-based study, we sourced data from 24 databases for 23 jurisdictions (either whole countries or regions of a country): Australia; Austria; Canada; Denmark; Finland; France; Germany; Hong Kong; Hungary; Israel; Italy; Japan; Latvia; Lithuania; the Netherlands; Norway; Scotland; Singapore; South Korea; Spain; Taiwan; the UK; and the USA. Our main outcomes were lifetime risk of type 2 diabetes, life expectancy in people with and without type 2 diabetes, and years of life lost to type 2 diabetes. We modelled the incidence and mortality of type 2 diabetes in people with and without type 2 diabetes in sex-stratified, age-adjusted, and calendar year-adjusted Poisson models for each jurisdiction. Using incidence and mortality, we constructed life tables for people of both sexes aged 20–100 years for each jurisdiction and at two timepoints 5 years apart in the period 2005–19 where possible. Life expectancy from a given age was computed as the area under the survival curves and lifetime lost was calculated as the difference between the expected lifetime of people with versus without type 2 diabetes at a given age. Lifetime risk was calculated as the proportion of each cohort who developed type 2 diabetes between the ages of 20 years and 100 years. We estimated 95% CIs using parametric bootstrapping. Findings: Across all study cohorts from the 23 jurisdictions (total person-years 1 577 234 194), there were 5 119 585 incident cases of type 2 diabetes, 4 007 064 deaths in those with type 2 diabetes, and 11 854 043 deaths in those without type 2 diabetes. The lifetime risk of type 2 diabetes ranged from 16·3% (95% CI 15·6–17·0) for Scottish women to 59·6% (58·5–60·8) for Singaporean men. Lifetime risk declined with time in 11 of the 15 jurisdictions for which two timepoints were studied. Among people with type 2 diabetes, the highest life expectancies were found for both sexes in Japan in 2017–18, where life expectancy at age 20 years was 59·2 years (95% CI 59·2–59·3) for men and 64·1 years (64·0–64·2) for women. The lowest life expectancy at age 20 years with type 2 diabetes was observed in 2013–14 in Lithuania (43·7 years [42·7–44·6]) for men and in 2010–11 in Latvia (54·2 years [53·4–54·9]) for women. Life expectancy in people with type 2 diabetes increased with time for both sexes in all jurisdictions, except for Spain and Scotland. The life expectancy gap between those with and without type 2 diabetes declined substantially in Latvia from 2010–11 to 2015–16 and in the USA from 2009–10 to 2014–15. Years of life lost to type 2 diabetes ranged from 2·5 years (Latvia; 2015–16) to 12·9 years (Israel Clalit Health Services; 2015–16) for 20-year-old men and from 3·1 years (Finland; 2011–12) to 11·2 years (Israel Clalit Health Services; 2010–11 and 2015–16) for 20-year-old women. With time, the expected number of years of life lost to type 2 diabetes decreased in some jurisdictions and increased in others. The greatest decrease in years of life lost to type 2 diabetes occurred in the USA between 2009–10 and 2014–15 for 20-year-old men (a decrease of 2·7 years). Interpretation: Despite declining lifetime risk and improvements in life expectancy for those with type 2 diabetes in many high-income jurisdictions, the burden of type 2 diabetes remains substantial. Public health strategies might benefit from tailored approaches to continue to improve health outcomes for people with diabetes. Funding: US Centers for Disease Control and Prevention and Diabetes Australia.